(untitled) (Libya Journal of Geographical Studies, 2023)
Countries are increasingly interested in the importance of the role of recreational services in the life of cities, due to their environmental impacts in reducing pollution and improving local climatic conditions, as they have psychological, health and economic benefits, making them one of the most important basic services to be provided in cities and not just a manifestation of well-being and in light of the rapid population and urban growth and urbanization witnessed in Taiz, which negatively affected its urban environment and increased the problem with horizontal urban sprawl, high land prices and low per capita. From parks and public parks, which led to the expansion of the use of residential, commercial and industrial land, at the expense of recreational services, which represent the main outlet of the population, which imposes the need to provide it as a factor for environmental rebalancing within the city of Taiz. The study therefore aimed to determine the pattern, shape and direction of the geographical distribution of recreational services in Taiz city and to assess its level of efficiency and efficiency and the amount of inability and planning the current and future needs of them, and the study recommends decision makers to apply their results to help them evaluate and plan recreational services in Taiz city and improve their efficiency and development in a balanced and sustainable manner to meet the need of its population present and future